Early selenium treatment for traumatic brain injury: Does it improve survival and functional outcome?. Issue 9 (September 2017) - Khalili, Hosseinali; Ahl, Rebecka; Cao, Yang; Paydar, Shahram; Sjölin, Gabriel; Niakan, Amin; Dabiri, Gholamreza; Mohseni, Shahin
Abstract: Background: Traumatic brain injury (TBI) is a major cause of death and debility following trauma. The initial brain tissue insult is worsened by secondary reactive responses including oxidative stress reactions, inflammatory changes and subsequent permanent neurologic deficits. Effective agents to improve functional outcome and survival following TBI are scarce. Selenium is an antioxidant which has shown to reduce oxidative stress. This study examines the effect of intravenous selenium (Selenase ® ) treatment in patients with severe TBI on functional outcome and survival in a prospective study design. Methods: Patients sustaining TBI were prospectively identified during a 12-month period at an academic urban trauma center. Study inclusion criteria applied were: age ≥18 years, blunt injury mechanism and admission to neurosurgical intensive care unit (NICU). Early deaths (≤48 h) and patients suffering extracranial injuries requiring invasive interventions or surgery were excluded. All consecutive admissions during a six-month period were administered intravenous Selenase ® for a maximum 10-day period and constituted cases. Patient demographics and outcomes up to six-months post-discharge were collected for analysis. Results: A total of 307 patients met inclusion criteria of which 125 were administered Selenase ® . Stepwise Poisson regression analysis identified five common predictors of poor functional outcome and in-hospital mortality: GCS ≤8, age ≥55 years, hypotension at admission, high Rotterdam score and invasive neurosurgical intervention. Selenase ® significantly reduced the risk of unfavourable functional outcomes, defined as GOS-E ≤4, at both discharge (adjusted RR 0.69, 95% CI 0.51–0.92, p = 0.012) and at six months follow-up (adjusted RR 0.61, 95% CI 0.44–0.83, p = 0.002). Following adjustment for significant group differences similar results were seen for functional outcome. Selenase ® did not improve survival (adjusted RR 1.12, 95% CI 0.62–2.02, p = 0.709). Conclusion: Intravenous Selenase ® treatment demonstrates a significant improvement in functional neurologic outcome. This effect is sustained at six months following discharge.